Excessive new origin firing underlies selective glioma stem cell cytotoxicity induced by replication stress response inhibition. (15th October 2021) - Clough, Emily; Strathdee, Karen; Carruthers, Ross
Abstract: Aims: Glioblastoma (GBM) is a treatment refractory cancer of extreme unmet need which exhibits treatment resistance due to a subpopulation of GBM cancer stem cells which have constitutive DNA damage response activation driven by elevated replication stress (RS). RS response inhibition is potently cytotoxic to GSC, however mechanistic understanding will be key to biomarker discovery and successful clinical translation. We investigated response to combined ATR and PARP inhibition (CAiPi) to gain mechanistic insight and inform biomarker development. Method: A panel of patient-derived GBM cell lines were cultured as stem enriched (GSCs) or stem depleted (bulk), to characterise response to combined ATR inhibition (VE821 5μM) and PARP inhibition (Olaparib 1μM), by CellTiter-Glo viability assay. Mechanistic investigations included immunofluorescence of 53BP1 nuclear bodies and DNA fibre analysis. Studies into the importance of PARP trapping included another PARPi Veliparib (1μM), and investigations into inhibition of origin firing used the CDK inhibitor Roscovitine. Results: Responses to CAiPi in a panel of primary paired GBM GSCs vs differentiated progeny were heterogenous. CAiPi is selectively GSC cytotoxic in a subpopulation of tumours. DNA fibre analysis identified increased new origin firing with PARPi, which was correlated with increased PARP trapping. Inhibition of origin firing by exposure to roscovitine rescued the CAiPi cytotoxic phenotype, suggesting origin firing has an important role in selective GSC cytotoxicity. A population of treatment-sensitive GSCs with increased numbers of 53BP1 nuclear bodies in G1 phase with CAiPi were identified, indicative of under-replication of DNA in S phase. Conclusion: Selective GSC cytotoxicity is induced by CAiPi via dysregulation of replication, by both DNA under-replication resulting in DNA lesions, and the novel finding of increased new origin firing in GSC due to PARPi.